Longevity in the 21st century: a global environmental perspective. (21st October 2011) - Dummer, Trevor J.B.; Halsall, Jamie P.; Cook, Ian G.
One of the great human success stories in the last few decades has been the marked increase in longevity in many, albeit not all, societies across the globe. Lifespans reaching into the 80s, 90s and 100s are becoming increasingly common, and forecasters predict even greater proportionate gains to come during the course of the 21st century. This article summarises the gains that have been, and continue to be, made then examines the extent to which these will continue in the face of climate change that will probably give rise to more frequent environmental disasters and threats in the future, as Malthusian and neo-Malthusian checks on longevity. Older people will themselves be among those groups most vulnerable to environmental disasters, and policies will be required to assist older people in many unstable environments around the globe in order to ensure their survival. Previous work on Asian longevity will be augmented by case studies of Hurricane Katrina and the recent Haiti earthquake in order to assess the validity of these generalisations.